2017
DOI: 10.1371/journal.pone.0176504
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between early onset severe intrahepatic cholestasis of pregnancy and higher risk of meconium-stained fluid

Abstract: BackgroundIntrahepatic cholestasis of pregnancy (ICP) is the commonest gestational liver disease. The risk of adverse fetal outcome has been associated with the severity of maternal hypercholanemia after diagnosis.ObjectiveTo investigate whether there is a relationship between the severity and timing of onset of hypercholanemia and the risk of meconium-stained amniotic fluid (MSAF) and adverse neonatal events.Study designThe study included 382 pregnancies complicated by ICP managed at a referral hospital in Bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 40 publications
4
38
0
Order By: Relevance
“…According to the literature, it seems that ICP patients have an increased risk of preeclampsia and gestational diabetes [6,7,9]. Our study also found that the rate of gestational diabetes in ICP patients was higher than in women with normal pregnancies, but there was no difference in preeclampsia.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…According to the literature, it seems that ICP patients have an increased risk of preeclampsia and gestational diabetes [6,7,9]. Our study also found that the rate of gestational diabetes in ICP patients was higher than in women with normal pregnancies, but there was no difference in preeclampsia.…”
Section: Discussionsupporting
confidence: 69%
“…The rate of cholestasis of pregnancy in our study was 2% and the rate of severe ICP was found to be 33% in all ICP patients. In previous studies, the incidence of cholestasis of pregnancy was 0.7-1.5% in the UK and severe ICP was observed in 15% of all ICP patients [6][7][8]. This ratio was found to be higher in our region.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…in her study showed a prevalence of 35.6% in primigravida patients and 64.4% in multigravida patients. 25 A local study at Agha khan hospital Karachi also showed a high prevalence of 57% among primigravidas. 26 The reason for this difference is not clear.…”
Section: Discussionmentioning
confidence: 98%
“…Higher risk of MSAF is associated with early onset of intrahepatic cholestasis of pregnancy and raised maternal serum bile acids (7) .…”
Section: …………………………………………………………………………………………………… Introduction:-mentioning
confidence: 99%